“INVESTMENT DECISION-MAKING AMONG FEMALE PROFESSIONALS IN BENGALURU: THE GOLD FACTOR” (CAHIERS MAGELLANES-NS, 2024)
In an era of more financial empowerment and independence, women are becoming a major force in the investment world. Bengaluru, known as India's Silicon Valley, has a large number of professional women who seek to grow and protect their wealth. Among the many investing options available, gold stands out as a particularly appealing choice. The underlying factors that shape the investment behaviour of working women in Bengaluru towards gold need to be explored, as the allure of gold as an investment vehicle has been a captivating subject of study.This study analyses how working women in Bengaluru invest in gold as an option. It examines the factors that affect their purchase of physical gold, such as culture, emotion, tangibility, and aesthetics. It also investigates how their investment knowledge and experience influence their preference for physical gold. The study uses a questionnaire to collect data from 128 working women who have invested in physical gold. The data is analysed using descriptive statistics, and regression analysis. The results show that investment knowledge, investment experience, cultural factors, emotional factors, tangible factors, and aesthetic factors affect their investment behaviour towards physical gold. The study also finds that investment experience has a positive and significant impact on their preference for physical gold. The study concludes that working women in Bengaluru prefer physical gold as an investment option and that their investment behaviour is influenced by various factors. The study provides some implications and recommendations for policy makers, marketers, and investors of gold.